Plant microbiota modified by plant domestication - Martínez-Romero E. (2020)
Human life became largely dependent on agricultural products after distinct crop-domestication events occurred around 10,000 years ago in different geographical sites. Domestication selected suitable plants for human agricultural practices with unexpected consequences on plant microbiota, which has notable effects on plant growth and health. Among other traits, domestication has changed root architecture, exudation, or defense responses that could have modified plant microbiota. Here we present the comparison of reported data on the microbiota from widely consumed cereals and legumes and their ancestors showing that different bacteria were found in domesticated and wild plant microbiomes in some cases. Considering the large variability in plant microbiota, adequate sampling efforts and function-based approaches are needed to further support differences between the microbiota from wild and domesticated plants. The study of wild plant microbiomes could provide a valuable resource of unexploited beneficial bacteria for crops. © 2020 Elsevier GmbH